Wind tunnel and computational study of the stoss slope effect on the aeolian erosion of transverse sand dunes - Faria, Raquel; Ferreira, Almerindo D.; Sismeiro, João L.; Mendes, João C.F.; Sousa, Antonio C.M. (Aeolian research, 2011)
To understand aeolian particle entrainment, it is important to take into account the surface slope, as most natural sand surfaces are not horizontal. The influence of slope angle on local friction velocity is the subject of this research. Three transverse triangular piles, with stoss slopes of 10°, 20°, and 32°, were tested experimentally, and modeled computationally. The wind tunnel experiments include two sets of tests: the first one consists of friction velocity measurements across the windward slope and the second set comprises the measurement of the sand dune longitudinal profile over time. The experimental tests were conducted at four undisturbed wind speeds ranging from 8.3 to 10.7m/s. The computational modeling was performed using a commercial CFD code, and it aimed to replicate the experimental conditions with the objective of evaluating its ability to predict the friction velocity across the windward slope. The numerical predictions of the friction velocity, for the initial longitudinal profile, show good agreement when compared to the experimental values. The region where the predicted friction velocity exceeds the threshold coincides quite well with the eroded area. The correlation between the vertical sand flux, across the stoss slope, calculated using the first eroded longitudinal profile, against the predicted friction velocity showed a cubic relation. The computational model, in view of the predicted results, seems to be a reliable tool for the estimation of the friction velocity for situations similar to those studied in this work.